EVALUASI KEBIJAKAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 11 TAHUN 2001 TENTANG PENATAAN DAN PEMBINAAN PEDAGANG KAKI LIMA DI KECAMATAN TAMPAN TAHUN 2016 - Sukri "; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Street vendors are informal sector economic actors who sell services or goods to meet the needs of the surrounding community while at the same time obtaining benefits from trading. The Regional Government is responsible for arranging and fostering street vendors so as not to disturb public order due to the large number of street vendors with the police unit of the civil service in Pekanbaru as a control apparatus. Mayor Regulation Number 114 of 2016 to appoint the Office of Industry and Trade which provides tasks and functions in the Market Sector to organize and foster street vendors. The problem statement from this research is how the effectiveness and responsiveness of the Regional Regulation of Pekanbaru City Number 11 Year 2001 concerning the Arrangement and Guidance of Street Vendors in Tampan Districts in 2016. The purpose of this study is to determine the effectiveness and responsiveness of Pekanbaru City Regulation Number 11 Year 2001 concerning Arrangement and Coaching of Street Vendors in Tampan Districts of 2016. The method used in this study is qualitative descriptive. Based on the results of the study showed that the need for evaluating the implementation of the policy of structuring and fostering street vendors due to the Regional Regulation of Pekanbaru City Number 11 of 2001 concerning the Arrangement and Coaching of Street Vendors has not been effective and responsive in managing and fostering street vendors to be efficient. Ideally, the area of Pekanbaru City should be supported by the availability of apparatus units for the Pekanbaru City Civil Service Police Unit. The Department of Industry and Trade by the Market Sector does not coordinate well causing the arrangement and guidance of street vendors outside the government market is not done well.Keywords: Policy Evaluation, Regional Regulations